Complication detection in MRI guided cardiac ablation: Atrial wall damage and hepatic oedema - Armando Fusco; Alessandra Luciano; Matteo Cesareni; Ermenegildo De Ruvo; Alessio Borrelli; Giuseppe Tufaro; Alessandro Maria Ferrazza; Marcello Chiocchi; Leonardo Calò; Matteo Stefanini (Radiology Case Reports, 2024)
Magnetic resonance imaging is a novel imaging technique for guiding electrophysiology based ablation operations for atrial flutter and typical atrial fibrillation. When compared to standard electrophysiology ablation, this innovative method allows for better outcomes. Intra-procedural imaging is important for following the catheter in real time throughout the ablation operation while also seeing cardiac architecture and determining whether the ablation is being completed appropriately utilizing oedema sequences. At the same time, intra-procedural imaging allows immediate visualization of any complications of the procedure. We describe a case of a 67 year old male underwent an isthmus-cavo-tricuspid magnetic resonance-guided thermoablation procedure for atrial flutter episodes. During the procedure we noted an atypical focal thinning of the right atrial wall at the isthmus cava-tricuspidal zone. The post-procedural Black Blood T2 STIR showed an area of hyperintensity at the hepatic dome and glissonian capsule, which was consistent with intraparenchymal hepatic oedema, in close proximity to the atrial finding. Given the opportunity to direct monitoring of adjacent tissues, we aim to highlight with our case the ability of magnetic resonance-guided cardiac ablation to immediately detect peri-procedural complications in the ablative treatment of atrial fibrillation.